A flare in the optical spotted in the changing-look Seyfert NGC 3516 - Ilic D (EDP SCIENCES S A, 2022)
Context. We present observations from the short-term intensive optical campaign (from September 2019 to January 2020) of the changing-look Seyfert NGC 3516. This active galactic nucleus is known to have strong optical variability and has changed its type in the past. It has been in the low-activity state in the optical since 2013, with some rebrightening from the end of 2015 to the beginning of 2016, after which it remained dormant.
Aims. We aim to study the photometric and spectral variability of NGC 3516 from the new observations in U- and B-bands and examine the profiles of the optical broad emission lines in order to demonstrate that this object may be entering a new state of activity.
Methods. NGC 3516 has been monitored intensively for the past 4 months with an automated telescope in U and B filters, enabling accurate photometry of 0.01 precision. Spectral observations were triggered when an increase in brightness was spotted. We support our analysis of past-episodes of violent variability with the UV and X-ray long-term light curves constructed from the archival Swift/UVOT and Swift/XRT data.
Results. An increase of the photometric magnitude is seen in both U and B filters to a maximum amplitude of 0.25 mag and 0.11 mag, respectively. During the flare, we observe stronger forbidden high-ionization iron lines ([FeVII] and [FeX]) than reported before, as well as the complex broad H alpha and H beta lines. This is especially seen in H alpha, which appears to be double-peaked. It seems that a very broad component of similar to 10 000 km s(-1) in width in the Balmer lines is appearing. The trends in the optical, UV, and X-ray light curves are similar, with the amplitudes of variability being significantly larger in the case of UV and X-ray bands.
Conclusions. The increase of the continuum emission, the variability of the coronal lines, and the very broad component in the Balmer lines may indicate that the AGN of NGC 3516 is finally leaving the low-activity state in which it has been for the last similar to 3 years.